The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/environments4010008
|View full text |Cite
|
Sign up to set email alerts
|

Response of Red-Backed Salamanders (Plethodon Cinereus) to Changes in Hemlock Forest Soil Driven by Invasive Hemlock Woolly Adelgid (Adelges Tsugae)

Abstract: Hemlock forests of the northeastern United States are declining due to the invasive hemlock woolly adelgid (HWA) (Adelges tsugae). Hardwood species replace these forests, which affects soil properties that may influence other communities, such as red-backed salamanders (red-backs) (Plethodon cinereus). This study examined the effects of HWA invasion on soil properties and how this affects red-backs at the Hemlock Removal Experiment at Harvard Forest, which consists of eight 0.8 ha plots treated with girdling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In recently harvested forests in West Virginia, P. cinereus expends more energy on body maintenance, although there were no consistent patterns related to body condition or invertebrate abundance (Homyack et al, 2011). In New York, Beier et al (2012) found a positive relationship between P. cinereus abundance and a well-defined calcium gradient, while in Massachusetts, Ochs & Siddig (2017) found P. cinereus was more prevalent in forests with lower soil pH, lower carbon to nitrogen (C:N) ratios, and lower temperatures. The authors note that the first two characteristics, low soil pH and low C:N ratios, are characteristic of hemlock stands, which used to be much more common within the range of P. cinereus prior to the arrival of hemlock wooly adelgid (Siddig et al, 2019).…”
Section: (I) Ecosystem Ecologymentioning
confidence: 96%
See 2 more Smart Citations
“…In recently harvested forests in West Virginia, P. cinereus expends more energy on body maintenance, although there were no consistent patterns related to body condition or invertebrate abundance (Homyack et al, 2011). In New York, Beier et al (2012) found a positive relationship between P. cinereus abundance and a well-defined calcium gradient, while in Massachusetts, Ochs & Siddig (2017) found P. cinereus was more prevalent in forests with lower soil pH, lower carbon to nitrogen (C:N) ratios, and lower temperatures. The authors note that the first two characteristics, low soil pH and low C:N ratios, are characteristic of hemlock stands, which used to be much more common within the range of P. cinereus prior to the arrival of hemlock wooly adelgid (Siddig et al, 2019).…”
Section: (I) Ecosystem Ecologymentioning
confidence: 96%
“…Another line of investigation has made connections between ecosystem changes or elemental gradients to P. cinereus populations or energetics (Homyack, Haas, & Hopkins, 2011;Beier et al, 2012;Ochs & Siddig, 2017). In recently harvested forests in West Virginia, P. cinereus expends more energy on body maintenance, although there were no consistent patterns related to body condition or invertebrate abundance (Homyack et al, 2011).…”
Section: (I) Ecosystem Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…Girdling and logging both resulted in a transformation from a deeply shaded evergreen coniferous forest with a sparse understory, to a deciduous hardwood forest with greater understory species abundance and richness (Orwig et al, 2013). This regime shift had cascading effects on salamanders (Ochs & Siddig, 2017;Siddig et al, 2016), moose and deer (Faison et al, 2016), small mammals (Degrassi, 2016), ants (Record et al, 2018), and macroarthropods (Sackett et al, 2011). Soil carbon storage and soil CO 2 efflux changed surprisingly little after hemlock loss (Finzi et al, 2014;Raymer et al, 2013), in contrast with findings of lower soil CO 2 efflux in the southern Appalachians after T A B L E 2 Summary of differences in the rate, magnitude, and persistence of change between the girdled and logged plots over 15 years.…”
Section: Persistent Differences In Canopy Tree Loss By Simulated Inse...mentioning
confidence: 99%